2021
DOI: 10.1038/s41598-021-82538-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the gut bacterial microbiome in people with type 2 diabetes mellitus and diabetic retinopathy

Abstract: Gut bacterial microbiome dysbiosis in type 2 Diabetes Mellitus (T2DM) has been reported, but such an association with Diabetic Retinopathy (DR) is not known. We explored possible link between gut bacterial microbiome dysbiosis and DR. Using fecal samples of healthy controls (HC) and people with T2DM with/without DR, gut bacterial communities were analysed using 16S rRNA gene sequencing and data analysed using QIIME and R software. Dysbiosis in the gut microbiomes, at phyla and genera level, was observed in peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(151 citation statements)
references
References 86 publications
3
121
1
Order By: Relevance
“…Recent studies demonstrated the alterations and possible application prospects of the gut microbiome in patients with other ocular neovascular diseases, such as DR (Das et al, 2021;Huang et al, 2021) and retinopathy of prematurity (Skondra et al, 2020). Das et al (2021) recognized a reduction in anti-inflammatory, probiotic and other bacteria that could be pathogenic in the microbiomes of patients with both diabetes mellitus and DR, compared to the healthy controls, and the changes observed in DR patients were more pronounced. Huang et al (2021) indicated the potential use of gut microbiota as a biomarker of DR, which could be helpful for diagnosis in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the alterations and possible application prospects of the gut microbiome in patients with other ocular neovascular diseases, such as DR (Das et al, 2021;Huang et al, 2021) and retinopathy of prematurity (Skondra et al, 2020). Das et al (2021) recognized a reduction in anti-inflammatory, probiotic and other bacteria that could be pathogenic in the microbiomes of patients with both diabetes mellitus and DR, compared to the healthy controls, and the changes observed in DR patients were more pronounced. Huang et al (2021) indicated the potential use of gut microbiota as a biomarker of DR, which could be helpful for diagnosis in clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resistant bacteria could be targeted specifically, clearing them from the infection and leaving antibiotic susceptible bacteria that can be eliminated by standard antibiotic treatments 17 . In addition, the technique could also be used for targeted microbiome engineering, highlighting the potential of CRISPR-Cas based medicine to not only treat infectious diseases but also multiple microbiome-related conditions such as diabetes 18 , obesity 19 and cancer 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was extracted from ∼150 mg of homogenized fecal pellets, and the quality of DNA was checked as described earlier. 13 17 …”
Section: Methodsmentioning
confidence: 99%
“…SILVA 138 SSU ( https://www.arb-silva.de/documentation/release-138/ ) was used as the reference OTU database to identify bacteria at 97% identity, and the assignment of taxonomy was made as described in our earlier studies. 17 , 25 Sparse OTUs (<0.001% of the total HQ reads) were not considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation